Synthesis of polycationic gemini-amphiphile based on spermine - E. А. Ivanova; Yu. I. Tokareva; N. G. Morozova; М. А. Maslov; V. V. Chupin (Тонкие химические технологии, 2012)
The synthesis of a polycationic gemini-amphiphile based on 1,2-di-O-tetradecylglycerol and a natural polyamine - spermine - was carried out.